Choosing the proper path: outcomes of subxiphoid vs. lateral intercostal approaches in the resection of anterior mediastinal masses - Leng, Xuechun; Chen, Mengzou; Zhang, Yang; Gao, Jian; You, Zhenbing; Hu, Zhongwu (Frontiers in Surgery, 2024)
BackgroundWhile the subxiphoid approach (SA) in thoracoscopic thymectomy offers benefits in terms of fat removal and pain reduction, it remains unclear which patients with anterior mediastinal masses benefit most from the subxiphoid vs. the lateral intercostal approach (LA).MethodsThis retrospective study analyzed patients treated for anterior mediastinal masses at our center from January 2019 to December 2023. Patients were categorized into two groups based on the surgical approach: SA (35 cases) and LA (56 cases). Demographic data, clinical characteristics, perioperative metrics, and short-term outcomes were compared.ResultsNinety-one patients were included, with diagnoses including thymic cysts (43), thymomas types A, AB, and B1 (24), B2 thymomas (18), thymic carcinoma (6).No significant differences were found between the groups in terms of gender, age, tumor size, body mass index, conversion to sternotomy, or blood loss. The LA group, however, experienced shorter surgical durations (P < 0.001), less drainage (P = 0.021), shorter hospital stays (P < 0.001), and lower hospitalization costs (P = 0.024). Pain scores on the visual analogue scale were similar between groups on the day of surgery and the first postoperative day.ConclusionThe findings suggest that the lateral intercostal approach is preferable for patients with thymic cysts and Masaoka stage I–II thymomas without myasthenia gravis due to its efficiency and cost-effectiveness.